Composition, Structure, and PGPR Traits of the Rhizospheric Bacterial Communities Associated With Wild and Cultivated Echinocactus platyacanthus and Neobuxbaumia polylopha - de la Torre-Hernández, María Eugenia; Salinas-Virgen, Leilani I.; Aguirre-Garrido, J. Félix; Fernández-González, Antonio J.; Martínez-Abarca, Francisco; Montiel-Lugo, Daniel; Ramírez-Saad, Hugo C. (Frontiers in Microbiology, 2020)
The Queretaro semi-desert in central Mexico is the most southern extension of the Chihuahua desert. This semi-arid zone shelters a vast cactus diversity with many endemic species. Currently, two cacti species from this semi-desert namely, Echinocactus platyacanthus and Neobuxbaumia polylopha are under a threat to their survival. So far, there are no reports on the bacterial communities associated with these plants. In this study, we assessed the structure and diversity of the rhizospheric bacterial communities associated with Echinocactus platyacanthus and Neobuxbaumia polylopha growing in wild and cultivated conditions. Samples of E. platyacanthus were also approached with culture-based methods in search of isolates with plant growth promoting abilities. Metagenomic DNA was extracted from rhizospheric samples and used for Illumina sequencing of the 16S rRNA gene. α-diversity and amplicon sequence variant (ASV) richness were higher in both groups of E. platyacanthus samples. All samples accounted for 14 phyla, and the major 6 were common to all treatments. The dominant phyla in all four sample groups were Actinobacteria and Proteobacteria. Analysis at family and genus levels showed association patterns with the cultivated samples from both species grouping together, while the wild samples of each cactus species were grouping apart. High abundance values of Rubrobacteraceae (15.9–18.4%) were a characteristic feature of wild E. platyacanthus samples. In total, 2,227 ASVs were scored in all 12 rhizospheric samples where E. platyacanthus samples showed higher richness with 1,536 ASVs. Regarding the growing conditions, both groups of cultivated samples were also richer accounting for 743 and 615 ASVs for E. platyacanthus and N. polylopha, respectively. The isolates from E. platyacanthus rhizosphere were mainly assigned to Bacilli and Gammaproteobacteria. In total 35 strains were assayed for PGPR traits (IAA and siderophore production, phosphate solubilization, and fungal growth inhibition). Strains obtained from plants growing in the wild displayed better PGPR characteristics, stressing that naturally occurring wild plants are a source of bacteria with diverse metabolic activities, which can be very important players in the adaptation of cacti to their natural environments.